Emerging nanotechnology power : nanotechnology R & D and business trends in the Asia Pacific Rim - Liu, Lerwen (World Scientific, 2009)
The world is witnessing the fastest economic growth in Asia. Nanotechnology is believed to revolutionize industry in years to come and will have a significant economic impact. This book summarizes the efforts of Asian economies in pursuing nanotechnology, and their determination to be world leaders in the industry and economic development in the 21st century. The book provides an overview of the latest nanotechnology policy, infrastructure, research and development highlights and business trends in 13 economies including Australia, China, Hong Kong, India, Indonesia, Japan, Korea, Malaysia, New Zealand, Singapore, Taiwan, Thailand and Vietnam. With contributions from the top policy makers, government R & D institution executives and distinguished scientists from the 13 economies in the Asia Pacific region, this is the first book ever to provide comprehensive information and insights on Asian capabilities in nanotechnology. It will draw great interest from government policy makers, economists, academics, industry professionals, and investors who are engaged in strategy making, R & D, investment and business development in Asia.